Efektivitas Penggunaan LKS Berbasis Keterampilan Generik Sains Terintegrasi Karakter untuk Kelas III Sekolah Dasar - 'Aini, Ninin Nun; Ashari, Ashari; Ngazizah, Nur (Institut Agama Islam Negeri Palopo, 2022)
This study aims to determine the effectiveness of LKS in training Integrated Science Generic Skills in Class III SD Theme 6 Energy and its Changes at SD Muhammadiyah Bayan. The research method used is quasi-experimental. The sample of this study used two classes as samples, namely the control class which opened 20 students and the experimental class which was carried out by 20 students. The research design used was the pretest and posttest groups. The instruments used are character observation, implementation of learning, and tests. The results of the study (1) the value of the character before being carried out with an average of 2.69 with good criteria and before doing 3.67 with very good criteria, (2) the value of generic science skills, namely from the pretest results with an average of 60.25 with good criteria and posttest results. with an average of 90.5 with very good criteria (3) the LKS t test analysis of the characters shows that Fcount > Ftable i.e. 2.655 > 1.73406, while the LKS t-test analysis on general science skills shows that Fcount > Ftable i.e. 12.769 > 1.73406 . It was concluded that there was a significant effect between LKS and generic science skills and class III characters in Theme 6 Energy and Its Changes.